What I say isn’t always what I do: Investigating differences in children’s reported and actual snack food preferences - Jones, Sandra C; Kervin, Lisa; Reis, Samantha; Gregory, Parri (International Journal of Child Health and Nutrition, 2012)
The current study sought to explore discrepancies between children’s stated snack food motivations and actual food choices, using the Implicit Association Test (IAT) as a measure of implicit attitudes towards ‘healthy’ and ‘unhealthy’ foods. Participants were children aged 6-12 years (n=118), from two primary schools on the South Coast of NSW, Australia – a public school in a semi-rural suburb south of a sea-side city and a public school in a largely residential northern suburb of the same city. The children completed a questionnaire about motivations for snack choices, participated in an activity, completed two further questionnaires, selected snack foods from an in-class store, and participated in two rounds of an IAT ‘game’ pairing pictures of snack foods with positive and negative words. As hypothesized, the majority of children reported ‘healthiness’ as their primary motivator for snack food choice, but when faced with an actual purchase decision predominantly chose unhealthy snacks. It appears that children may have internalized the ‘moral’ values attributed to healthy and unhealthy foods and that this process influences both their explicit and implicit attitudes. However, their actual food choices are likely to be influenced by other factors, and thus more complex to understand and influence.